A revitalização do Museu de Arte de Santa Maria: história, memória e patrimônio cultural - Souza, Marcio Andrei Flores (2016)
In this research we present the results of the dissertation for the Professional graduate program in Cultural Heritage of the Federal University of Santa Maria.This project arose from the reintegration of the history of this museum institution, making it possible to analyze and identify all its revitalization process, protection and preservation, and its importance to the history, memory and cultural heritage of this city.This research also promotes understanding of the role of museums in society as a research institution, teaching and education, highlighting aspects such as memory, belonging to the material culture and immaterial providing a vast heritage.Because we understand the museum as an active institution, dynamic and diverse, with a suitable physical environment, educational activities, temporary exhibitions, traveling and long lasting.In this way we can see the museums and research centers, interpretation and cultural preservation, with its diversified museographies and its expanded possibilities in identity construction field and insight critical about the visual arts and the appropriate and correct museum processes revealing new realities in conservationist culture and preservationist, and these are also topics covered in this work.